The association between ethnicity and vaginal microbiota composition in Amsterdam, the Netherlands - Borgdorff, Hanneke; van der Veer, Charlotte; van Houdt, Robin; Alberts, Catharina J.; de Vries, Henry J.; Bruisten, Sylvia M.; Snijder, Marieke B.; Prins, Maria; Geerlings, Suzanne E.; Schim van der Loeff, Maarten F.; van de Wijgert, Janneke H. H. M. (PLOS ONE, 2017)
Objective To evaluate whether ethnicity is independently associated with vaginal microbiota (VMB) composition in women living in Amsterdam, the Netherlands, as has been shown for American women. Methods Women (18–34 years, non-pregnant, N = 610) representing the six largest ethnic groups (Dutch, African Surinamese, South-Asian Surinamese, Turkish, Moroccan, and Ghanaian) were sampled from the population-based HELIUS study. Sampling was performed irrespective of health status or healthcare seeking behavior. DNA was extracted from self-sampled vaginal swabs and sequenced by Illumina MiSeq (16S rRNA gene V3-V4 region). Results The overall prevalence of VMBs not dominated by lactobacilli was 38.5%: 32.2% had a VMB resembling bacterial vaginosis and another 6.2% had a VMB dominated by Bifidobacteriaceae (not including Gardnerella vaginalis), Corynebacterium, or pathobionts (streptococci, staphylococci, Proteus or Enterobacteriaceae). The most prevalent VMB in ethnically Dutch women was a Lactobacillus crispatus-dominated VMB, in African Surinamese and Ghanaian women a polybacterial G. vaginalis-containing VMB, and in the other ethnic groups a L. iners-dominated VMB. After adjustment for sociodemographic, behavioral and clinical factors, African Surinamese ethnicity (adjusted odds ratio (aOR) 5.1, 95% confidence interval (CI) 2.1–12.0) and Ghanaian ethnicity (aOR 4.8, 95% CI 1.8–12.6) were associated with having a polybacterial G. vaginalis-containing VMB, and African Surinamese ethnicity with a L. iners-dominated VMB (aOR 2.8, 95% CI 1.2–6.2). Shorter steady relationship duration, inconsistent condom use with casual partners, and not using hormonal contraception were also associated with having a polybacterial G. vaginalis-containing VMB, but human papillomavirus infection was not. Other sexually transmitted infections were uncommon. Conclusions The overall prevalence of having a VMB not dominated by lactobacilli in this population-based cohort of women aged 18–34 years in Amsterdam was high (38.5%), and women of sub-Saharan African descent were significantly more likely to have a polybacterial G. vaginalis-containing VMB than Dutch women independent of modifiable behaviors.